Fas-Fas Ligand Interplay in the Periphery of Salivary Gland Carcinomas as a New Checkpoint Predictor for Disease Severity and Immunotherapy Response - Zuzana Strizova; Martin Kuchar; Linda Capkova; Martin Komarc; Jiri Skrivan; Jirina Bartunkova; Jan Plzak; Daniel Smrz (Biomedicines, 2021)
Salivary gland carcinomas (SGCs) are extremely morphologically heterogeneous, and treatment options for this disease are limited. Immunotherapy with immune checkpoint inhibitors (ICIs) represents a revolutionary treatment approach. However, SGCs remain largely resistant to this therapy. An increasing body of evidence suggests that resistance to ICI therapy is modulated by the Fas (CD95)–Fas ligand (FasL, CD178) interplay between tumor cells and immune cells. In this study, we examined the Fas–FasL interplay between tumor cells and tumor-infiltrating immune cells (TIICs) in the center and periphery of SGCs from 62 patients. We found that the Fas-expressing tumor cells accumulated in the center of SGC tumors with increasing tumor stage. Furthermore, this accumulation occurred regardless of the presence of TIICs expressing high levels of FasL. On the contrary, a loss of Fas-expressing TIICs with increasing tumor stage was found in the tumor periphery, whereas FasL expression in tumor cells in the tumor periphery correlated with tumor stage. These data suggest that SGC cells are resistant to FasL-induced apoptosis by TIICs but could utilize FasL to eliminate these cells in high-stage tumors to provide resistance to immunotherapy.